HUBUNGAN FAKTOR IBU SAAT HAMIL TERHADAP BERAT BADAN LAHIR DI PRAKTIK MANDIRI BIDAN (PMB) SYAFRIANI KECAMATAN NIBONG KABUPATEN ACEH UTARA - Elizar Elizar; Amelia Nur Hidayanti (Universitas An Nuur, 2023)
Background: A baby's birth weight at birth is an important indicator of a child's vulnerability to disease, risk of disease, occurrence of disease in children and also predicts the child's health, growth, psychosocial development and chances of survival. Low birth weight babies are at risk of stunting. Risk factors associated with the incidence of LBW include socio-economic and maternal characteristics.Method: This research is an observational study with a cross-sectional approach which aims to analyze the relationship between maternal factors and birth weight in the Syafriani Independent Midwife Practice (PMB), Nibong District, North Aceh Regency. The sample in this study consisted of 41 post-partum mothers, where the sampling technique was determined by total sampling, namely all post-partum mothers recorded in medical records from January to February 2023. The sample criteria were mothers who gave birth to live babies and gestational age at term at the time of delivery.Results: From the results of analysis tests carried out, maternal factors including age, family income, complaints during pregnancy and parity were related to the baby's birth weight where the p-value was <0.05. The variables of maternal education, maternal occupation, history of miscarriage and pregnancy examination were not related to the baby's birth weight with a p-value >0.05. From the results of the multivariate analysis test using multiple logistic regression, it was found that only mothers who experienced complaints during pregnancy had a partial effect on birth weight with a p-value <0.05.Conclusion: The results of the study concluded that maternal factors related to birth weight included age, family income, complaints during pregnancy and parity. Keywords: Birth Weight, During pregnancy,Maternal Factors,